2004
DOI: 10.1021/es0354667
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nitroglycerin with Elemental Iron:  Pathway, Kinetics, and Mechanisms

Abstract: Nitroglycerin (NG) is a nitrate ester used in dynamites, propellants, and medicines and is therefore a common constituent in propellant-manufacturing and pharmaceutical wastewaters. In this study we investigated the reduction of NG with cast iron as a potential treatment method. NG was reduced stepwise to glycerol via 1,2- and 1,3-dinitroglycerins (DNGs) and 1- and 2-mononitroglycerins (MNGs). Nitrite was released in each reduction step and was further reduced to NH4+. Adsorption of NG and its reduction produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 64 publications
2
49
0
Order By: Relevance
“…This is in line with the observation made earlier by Capellos et al (1984) on the absence of the partially denitrated DNGs and MNGs from NG hydrolysis (pH 12). Likewise we did not observe the fully denitrated NG product glycerol which is known to be the final product of NG reaction with Fe(0) (Oh et al, 2004) and frequently found during biodegradation of the nitrate ester (Wendt et al, 1978;Servent et al, 1991;Meng et al, 1995;Marshall and White, 2001). When glycerol was allowed to react under the same conditions (pH 9) the chemical stayed intact indicating that glycerol is not a product of NG hydrolysis.…”
Section: Intermediates and Products Distributionsupporting
confidence: 48%
See 2 more Smart Citations
“…This is in line with the observation made earlier by Capellos et al (1984) on the absence of the partially denitrated DNGs and MNGs from NG hydrolysis (pH 12). Likewise we did not observe the fully denitrated NG product glycerol which is known to be the final product of NG reaction with Fe(0) (Oh et al, 2004) and frequently found during biodegradation of the nitrate ester (Wendt et al, 1978;Servent et al, 1991;Meng et al, 1995;Marshall and White, 2001). When glycerol was allowed to react under the same conditions (pH 9) the chemical stayed intact indicating that glycerol is not a product of NG hydrolysis.…”
Section: Intermediates and Products Distributionsupporting
confidence: 48%
“…When nitrite was microwave heated at pH 9 the anion stayed intact indicating that the anion did not reduce to ammonia as observed during treatment of NG with Fe(0) where the three -NO 2 groups in the nitrate ester reduced to ammonia (Oh et al, 2004). The same nitrite control did not give nitrate during microwave-assisted hydrolysis, indicating that nitrite and nitrate originated from NG independently during NG hydrolysis.…”
Section: Intermediates and Products Distributionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similar to GAC [34,35], biochar has been proposed as an adsorbent to decrease the concentrations and bioavailability of organic and metallic pollutants [17,36,37]. The present study further suggests that biochar may also be applied to promote the degradation of organic compounds including agrochemicals, explosives, and potentially other nitrogenous compounds such as azo dyes [38] and nitrate esters [26,39]. For example, in shooting ranges, proving grounds, and other military installations where soil and groundwater are contaminated with explosives, biochar may be used to accelerate the breakdown of these compounds.…”
Section: Possible Reaction Mechanisms and Environmental Implication Omentioning
confidence: 57%
“…Other physico-chemical remediation technologies for the removal of NG from the environment include oxidation, composting, phytoremediation, biodegradation (Pandey et al, 2007), iron reduction (Oh et al, 2004), and sorption using nano-structured silica based materials (Saad et al, 2010). However, none of these technologies are efficacious in removing energetic residues from soil, which can pose exposure risks for human and ecological receptors, such as terrestrial plants.…”
mentioning
confidence: 99%